Can the Stroop effect serve as the gold standard of conflict monitoring and control? A conceptual critique - Algom, Daniel; Fitousi, Daniel; Chajut, Eran (Memory & cognition, 2022)
The Stroop effect has been a key to the assay of selective attention since the time of the epoch-making study by J.R. Stroop almost a century ago. However, recent work based on computational modeling and recording of brain activations ignored the primary meaning of the Stroop effect as a measure of selectivity—with the Stroop test losing its raison d’être. Espousing the new framework, numerous studies in the past 20 years conceived performance in the Stroop task in terms of conflict-induced adjustments governed by central control on a trial-to-trial basis. In the face of this tsunami, we try to convince the reader that the Stroop effect cannot serve as a testing ground for conflict-monitoring and control, because these constructs are fundamentally unsuited to serve as a candidate theory of Stroop processes. A range of problems are discussed that singly and collectively pose grave doubts regarding the validity of a control and conflict monitoring account in the Stroop domain. We show how the key notion of conflict is misconstrued in conflict-monitoring models. Due to space limitations and for sake of wider accessibility, our treatment here cannot be technical.